Simplified approach towards DES (International Journal of Engineering and Computer Science, 2014)
The paper is a short discussion on one of the most important encryption technique ever since it was deduced, this technique utilizes the symmetric key algorithm of Network Security. The symmetric key algorithm is an algorithmwhich makes utilization two keys a public key and a private key so as to limit the data access and thus maintain the much needed secrecy of data.In symmetric key encryption algorithm the private key is the secret key as it rests with the sender and receiver only, this private key is responsible for the secrecy of data. Before we move onto detailed understanding of the algorithm it is necessary to know where is it being implemented or where you will get to see it and the answer to this question is network devices such as modem, routers, bridges, gateway, repeater hubs, and switches and any other device which involves transfer of data that is needed to be kept secret during its transmission to receiver.